Study on site selection for a cruise home port in the Yangtze River Delta region from the perspective of safety. (23rd July 2022) - Su, Zhaoqian; Xiao, Yingjie
Abstract: To improve the safety of cruise tourism in the Yangtze River Delta region (YRD), a new cruise ship home port is needed. This paper studies the process for selection of a site for the new cruise home port. Through analysis of previous cases of cruise tourism safety accidents, it is found that the basic situation of the cruise port, such as the channel, the port, logistics support and scenic places to visit, is important to cruise operation safety. An index system of site selection for a cruise home port is established, and the optimal choice of location for a regional cruise home port – between Shanghai, Zhoushan and Nantong – is analysed by the analytic hierarchy process (AHP). The research shows that the order of preferred site for the cruise home port is Zhoushan, then Shanghai and, third, Nantong. This paper can provide a reference for the layout of the whole industry chain of the cruise economy in the YRD in the future. This will promote the integration of development of the YRD, and enhance the regional connectivity and policy system efficiency in the YRD.